Parametric estimation for partly interval-censored failure time data under Weibull distribution - Mohammad Alharpy, Azzah; Ibrahim, Noor Akma (Scientific Publishing Center, University of Bahrain, 2014)
This article discusses the parametric estimation in the existence of partly interval-censored failure time data. Partly interval-censored failure time data is composed of exact observations and interval-censored observations. This phenomenon often happens in clinical trials and health studies that are followed by periodic follow-ups. We have constructed a parametric estimation for this kind of failure time data under Weibull distributions by using direct approach (without imputation) and indirect approach (with multiple imputation technique). Simulation studies are established to assess the proposed estimate for survival function and to illustrate the difference between the two approaches. The simulation results indicate that the presented procedure works well for both approaches but the estimate under the indirect approach is better than the estimate under direct approach. A modified secondary data set from breast cancer study is used to illustrate the proposed estimation.